Pembuatan Etanol Dari Rumput Gajah (Pennisetum purpureum schumach) Menggunakan Metode Hidrolisis Asam dan fermentasi Saccharomyces cerevsiae - Hafni Indriati Nasution; Ratna Sari Dewi; Primajogi Hasibuan (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. Elephant grass (Pennisetum purpureum schumach) not fully utilized by the people in North Sumatera. Though Elephant Grass containing lignocellulose namely cellulose, hemicellulose and lignin, which can be utilized as a valuable product that is as bioethanol. This research aims to study the benefits of elephant grass (Pennisetum purpureum schumach) to be made by the hydrolysis and ethanol fermentation to determine the effect of sampling sites on the cellulose content of elephant grass (Pennisetum purpureum schumach) is the area Lubuk Pakam, Tuntungan and Stabat; the influence of an acid catalyst H2SO4 and HCl for hydrolysis and fermentation time 2, 4, 6 and 8 days to produce the optimum ethanol. The results showed that the highest cellulose content is sampled area Lubuk Pakam which is further used in the process of hydrolysis. A better catalyst in the process of hydrolysis to produce ethanol that is optimum HCl and optimum fermentation time to produce the highest ethanol content is 6 days with HCl catalyst as much as 27.83%. Keywords: elephant grass, cellulose, catalyst, hydrolysis, fermentation, destilation